2019
DOI: 10.1109/access.2019.2906379
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Oil-Paper Insulation Aging Using Frequency Domain Spectroscopy and Moisture Equilibrium Curves

Abstract: Moisture content and aging of oil-paper insulation are two important factors that cause deterioration of the insulation performance of power transformers. The water molecules and aging products are polar, which affects the dielectric response characteristics of the insulation system. Currently, the dielectric response testing technology has realized non-destructive evaluation of the moisture content of transformer insulation. However, the changes in the dielectric response caused by aging products are easily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…In 2019, Yang et al [4] have suggested a new technique exploiting FDS and the water balance qualities of oil-paper insulation, to calculate the aging state of oil-paper insulation. To estimate the moisture content of the insulating paper, FDS curves were utilized, and oil samples were used to measure the moisture substance of the oil.…”
Section: A Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Yang et al [4] have suggested a new technique exploiting FDS and the water balance qualities of oil-paper insulation, to calculate the aging state of oil-paper insulation. To estimate the moisture content of the insulating paper, FDS curves were utilized, and oil samples were used to measure the moisture substance of the oil.…”
Section: A Related Workmentioning
confidence: 99%
“…Yet, it is having a challenge i.e., the areas are concentrated in dielectric, and in wave frequencies, the substrate loss might become inadequately high. FDS [4] calculates the contents of unknown data accurately using mathematical analysis algorithm, and provides consistent data. Nevertheless, there are some objections like the extent of aging of oil-paper insulation couldn't be calculated.…”
Section: B Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Where α i and β i are called the Lagrange operator. If Equation (6) satisfies the conditions obtained by Lagrange vertical multiplication shown in Equation 7, Equation (5) can be converted to the dual form shown in Equation (8).…”
Section: The Introduction Of Svmmentioning
confidence: 99%
“…Power transformers perform a vital task of transforming electrical energy in power systems, and the condition evaluation of its internal oil/paper system has attracted wide attention [ 1 , 2 , 3 , 4 , 5 , 6 ]. In recent years, a prevailing method of moisture determination is the so-called frequency domain spectroscopy (FDS) [ 7 , 8 , 9 , 10 ] technique, which is also called dielectric frequency response (DFR) technique. The condition assessment of transformer oil-immersed polymer insulation based on FDS could be realized by the following steps: Firstly, extracting feature parameters that could reflect the insulation conditions of oil-immersed insulation from the measured FDS data.…”
Section: Introductionmentioning
confidence: 99%